The Growth of Lemongrass (Cymbopogon nardus (L.) RENDLE) in Agroforestry and Monoculture System on Post-Coal Mining Revegetation Land - Nurheni Wijayanto; Irdika Mansur; Trikoesoemaningtyas; Anna Juliarti (Jurnal Manajemen Hutan Tropika, 2021)
Lemongrass (Cymbopogon nardus) as cover crop was suitable planted with agroforestry and monoculture system on post-coal mining revegetation land. The study investigated the influence of planting system, varieties, and plant spacing against the lemongrass growth on post-coal mining land under the agroforestry and monoculture system. Two lemongrass varieties were planted under on both planting systems. The growth variables of lemongrass measured were the tillers number per clump, leaf length, and canopy width. The results showed that the planting system and lemongrass varieties were able to increase the growth of lemongrass. Plant spacing treatment was able to increase the tillers number per clump. The agroforestry system was able to increase leaf length and canopy width of lemongrass. However, monoculture system was able to increase the tillers number per clump. The G2 variety had better growth on all measured variables either in agroforestry and monoculture system compared to Sitrona 2 Agribun variety. The plant spacing of 0.5 m × 0.5 m had greater tillers number per clump of lemongrass compared to plant spacing of 1 m × 1 m.